Comparison between state feedback and variable structure control of Magnetically Suspended Balance Beam (MSBB) system - Fijay, Fauzi; Ismail, Daut; Abdul Rashid, Husain; Mohamad Noh, Ahmad (Universiti Teknologi Malaysia (UTM), 2008)
Organized by Universiti Teknologi Malaysia (UTM), 28th - 29th May 2007 at Johor Bahru, Johor.